Incentive-Based Interventions - Uri Gneezy; Agne Kajackaite; Stephan Meier (The Handbook of Behavior Change, 2020)
This chapter provides a framework for how incentives affect behavior change. Economic theory is built on the premise that incentives matter, but empirical evidence shows the effect of incentives on behavior is more complicated than predicted by the basic law of demand. Our framework highlights four potential “channels” through which incentives can affect behavior change: First, incentives can help create “desirable” or “adaptive” habits by building up the stock of behavior. Increasing recent experience makes current behavior less costly and more enjoyable. Second, incentives can help “kill” undesirable or maladaptive habits by reducing the stock of behavior. Decreasing recent experience makes current behavior costlier and less enjoyable. Third, incentives can help counter present bias. Using frequent and regular incentives helps change behavior. Fourth, incentives can help remove barriers to change. Using incentives to reduce switching costs makes uptake of the desired behavior or activity cheaper or even free. These four channels and the supporting empirical evidence for them have implications for how incentive-based interventions work and provide guidance on how best to design them for optimal efficacy.
Keywords: 300; tangible rewards; intangible rewards; neoclassical economic theory; creating habits; breaking habits; regular and upfront incentives; removing barriers; behavior stock; present bias; reducing switching costs